Purification of sewage from salts of heavy metals by natural zeolite - Petrushka, I. M.; Pashuk, A. V.; Tarasovych, O. D. (Видавництво Львівської політехніки, 2014)
It is investigated prospect of using of natural zeolite for purification of sewages from salts of heavy metals. It is well-proven that maintenance of heavy metals in purified sewage reply requirements of SNIP for drinking-water in Ukraine. Досліджено перспективність використання природного цеоліту для очищення стічних вод від солей важких металів. Доведено, що вміст важких металів у очищеній стічній воді відповідає вимогам СНиП на питну воду в Україні.
Keywords: a zeolite; adsorption; sewage; heavy metals; цеоліт; адсорбція; стічні води; важкі метали